Biallelic ITGB4 variants in familial pyloric atresia without epidermolysis bullosa: Report of two families with five siblings. Issue 11 (17th August 2021) - Soyer, Tutku; Karaosmanoglu, Beren; Taskiran, Ekim Z.; Kiper, Pelin Özlem Şimşek; Karnak, İbrahim and Boduroğlu, Koray and Utine, Gülen Eda
Abstract: Pyloric atresia (PA) is a rare gastrointestinal anomaly that occurs either as an isolated lesion or in association with other congenital or hereditary anomalies. Familial occurrence of PA with epidermolysis bullosa (EB) has been well documented and variants in ITGA6, ITGB4, and PLEC are known to cause EB with PA. However, no gene variants have been defined in familial isolated PA. Five siblings with familial isolated PA are presented that suggest biallelic ITGB4 variants may underlie the development of PA without EB. Five siblings from two unrelated families with isolated PA were studied with exome sequencing (ES) to identify the genetic etiology in isolated familial cases. Exome sequencing was performed in one affected patient from each family. Validation and segregation studies were done by Sanger sequencing. Parents were first cousins in one family but there was no consanguinity in the other family. Type‐2 PA was detected in both families and none of the probands had associated anomalies. All patients underwent successful gastroduodenostomy and have been under follow‐up uneventfully. All patients had biallelic ITGB4 variants, c.2032G > T p.(Asp678Tyr) being a novel one. Biallelic ITGB4 variants may underlie the development of PA without associated EB. Further detection of variants in this gene may establish any possible genotype–phenotype correlations.